Franchising and Privatization - Dnes, Antony W. (World Bank, Washington, DC, 2012)
Increasing private sector participation to improve the efficiency of infrastructure services is a growing trend around the world. Some elements of most infrastructure activities exhibit "natural monopoly" characteristics, meaning that one or more services or products can be produced most cheaply by a single firm. This raises the issues of organizing an infrastructure industry so as to gain the advantages of production by a single firm, without encouraging monopolistic conduct. This Note discusses a franchise approach to problems of natural monopoly--franchise bidding schemes--proposed by Sir Edwin Chadwick, a Victorian social reformer and later promoted by Harold Demsetz in the United States. The essential idea is that monopoly franchises could be auctioned off to the bidder offering the most attractive terms. Competition through bidding ensures minimum selling prices because the winning franchise will lower prices until revenues just cover costs. Franchise schemes also may avoid pitfalls associated with traditional regulation of such industries or with their nationalization. The Note also discusses the advantages of a franchise system and the importance of contract design to a successful franchise system.